2011
DOI: 10.1073/pnas.1103605108
|View full text |Cite
|
Sign up to set email alerts
|

The former annotated human pseudogene dihydrofolate reductase-like 1 ( DHFRL1 ) is expressed and functional

Abstract: Human dihydrofolate reductase (DHFR) was previously thought to be the only enzyme capable of the reduction of dihydrofolate to tetrahydrofolate; an essential reaction necessary to ensure a continuous supply of biologically active folate. DHFR has been studied extensively from a number of perspectives because of its role in health and disease. Although the presence of a number of intronless DHFR pseudogenes has been known since the 1980s, it was assumed that none of these were expressed or functional. We show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 35 publications
(46 reference statements)
1
33
0
Order By: Relevance
“…5A and B). DHFR catalyzes the reduction of dihydrofolate to tetrahydrofolate, which is an essential cofactor for thymidylate biosynthesis by TS (35), and TK1 is an essential kinase of the salvage pathway for thymidylate biosynthesis (33). Consistent with this, following oxaliplatin treatment we observed a significant decrease in the level of dTTP in the dNTP pool (Fig.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…5A and B). DHFR catalyzes the reduction of dihydrofolate to tetrahydrofolate, which is an essential cofactor for thymidylate biosynthesis by TS (35), and TK1 is an essential kinase of the salvage pathway for thymidylate biosynthesis (33). Consistent with this, following oxaliplatin treatment we observed a significant decrease in the level of dTTP in the dNTP pool (Fig.…”
Section: Discussionsupporting
confidence: 74%
“…In addition, the salvage thymidylate biosynthesis pathway, which is initiated by TK1-mediated phosphorylation of thymidine, is another route for dTTP biosynthesis (33). We focused on three genes encoding enzymes of the thymidylate biosynthesis pathway, DHFR, TK1, and TS, whose promoters have architectures similar to those of genes involved in the G 1 -S transition, including DUT (34), and whose transcript levels during cell-cycle progression are regulated by Sp1 and E2F1 (35)(36)(37). The expression of DHFR (Fig.…”
Section: Oxaliplatin Induces Pri-mir-34a Before Repression Of Dut-n Ementioning
confidence: 99%
“…21), indicating that the contribution of ADAR1 to resistance is not different between MCF-7 and A549 cells. It has been reported that dihydrofolate reductase like 1, whose gene is known as pseudogene DHFRP4, is expressed and has same function as DHFR in folate metabolism (McEntee et al, 2011). It is possible that this enzyme may complement the decreased expression of DHFR by ADAR1 knockdown, leading to residual resistance to methotrexate in these cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a second DHFR-like enzyme, DHFRL1, has been identified (28,29), but it has much lower enzyme activity than DHFR (28) and is unlikely to account for the reported differences in enzyme activity between individuals (25). This points toward common polymorphisms that control the regulation and expression of the DHFR gene.…”
Section: Discussionmentioning
confidence: 92%